Pengaruh Rendaman Air Kencur Terhadap Oedema di Tungkai Pada Ibu Hamil Trimester III - Rini Hariani Ratih; Yusmaharani Yusmaharani (Jurnal Ilmu Kesehatan Abdurrab, 2024)
Background: Edema or swelling due to fluid accumulation in the body often occurs in the extremities, especially in the legs, occurring in around 80% of pregnancies. Carrying out therapy by soaking the feet in warm water mixed with galangal is one of the non-medical measures that can be carried out on pregnant women, with ingredients that are easy to get at the nearest shop. The aim of this study was to determine the effect of galangal water immersion on edema in the legs in third trimester pregnant women. The research method uses the Quasy Experiment type of research. The design used is One Group Pre Test and Posttest. This research was conducted at the Pratama Guava Rose Clinic. Tools and materials used kencur and observation sheet. The population in this study was 13 respondents, sampling using Quota sampling, namely a sampling technique based on criteria set by the researcher. The data sources used are primary data and secondary data. Data analysis used univariate and bivariate before carrying out the bivariate test, a parametric test was carried out, namely the normality test of normally distributed data, namely using the T-Dependent test. The research results show the effect of galangal water immersion on edema in the legs in pregnant women in the third trimester. Significance value < 0.005 with P value = 0.001 (Ha accepted). Conclusion There is an effect of galangal water immersion on edema in the legs in third trimester pregnant women at the Pratama Jambu Mawar Clinic